2020
DOI: 10.1002/ejp.1563
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and pain profiles in persons with patellofemoral pain as the primary symptom

Abstract: Background Patellofemoral pain (PFP) is defined biomechanically, but is characterized by features that fit poorly within nociceptive pain. Mechanisms associated with central sensitization may explain why, for some, symptoms appear nociplastic. This study compares psychological and somatosensory characteristics between those with persistent PFP and controls. Methods A total of 150 adults with PFP were compared to 61 controls. All participants completed a survey evaluating participant characteristics, PFP‐relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 91 publications
1
26
0
1
Order By: Relevance
“…In one study, 49% of the PFP group (total n for PFP group=151) reported stopping normal activity due to their knee pain. 43 Body mass index is reported in eight studies, and the PFP group was only significantly higher in one study. 41 Six of the included studies assessed only females, 28,36-40 while nine assessed mixed-sex cohorts, 27,41-43,47,48,52 and none assessed only males.…”
Section: Participant Characteristicsmentioning
confidence: 96%
See 4 more Smart Citations
“…In one study, 49% of the PFP group (total n for PFP group=151) reported stopping normal activity due to their knee pain. 43 Body mass index is reported in eight studies, and the PFP group was only significantly higher in one study. 41 Six of the included studies assessed only females, 28,36-40 while nine assessed mixed-sex cohorts, 27,41-43,47,48,52 and none assessed only males.…”
Section: Participant Characteristicsmentioning
confidence: 96%
“…A systematic review was conducted for data obtained that could not be pooled due to a low number of total studies, or differences in methods that did not allow for pooled results. Seven studies were included in the systematic review, two assessed thermal pain thresholds 43,45 and five assessed pain mapping.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations